The Concept and Important Importance of Intensity in Linguistics - Rustamova Shakhnoza Abdurakhimovna (Academia One, 2024)
Linguistics, as a scientific discipline, focuses on the study of language and its structure. Within this field, one of the fundamental concepts is intensity, which pertains to the level of strength, force, power, or significance of a linguistic element, be it a word or a sentence. The role of intensity in communication and language comprehension is pivotal, and it holds a crucial position in linguistic analysis and interpretation. In the realm of linguistics, intensity can manifest itself in various ways, including stress, emphasis, and intonation. These linguistic attributes have a profound impact on the meaning and understanding of a linguistic expression, making them indispensable for effective communication and comprehension. This article aims to delve into the concept of intensity in linguistics, highlighting its utmost importance and exploring its implications for the study and analysis of language
Keywords: linguistic means; attributes; qualities